Organizational Change in Banking: Potential and Future Research Opportunities - Pujianto, Wahyu Eko; Purwono, Rudi; Lastuti, Nunuk Dyah Retno (RSF Conference Series: Business, Management and Social Sciences, 2023)
This research aims to map the topic of organizational change in various scientific fields, especially in the banking sector. The research method used is quantitative with a descriptive approach.The research data were analyzed using bibliometric techniques. Documentation techniques and literature studies in this study were obtained through the Scopus database with the keywords used in the search in the Scopus database, namely "organizational change" and "banking" since 2000-2023, the subject area is limited to"business, management and accounting", "economic, econometric and finance", document type "article", source type "journal", language "English". Journal articles found in the initial stage of the search were 80 articles, then 42 articles were excluded because they were irrelevant and could not be fully accessed, and 38 articles could be used in the study. Analysis in this study was carried out using Vosviewer software. The results of this study indicate the existence of a network of keywords between one study and another. Further, the results of this study indicate that "organizational change" is one of the most frequently used keywords in previous studies. However, "organizational change" in the banking sector is still not widely done. Only 38 relevant articles are related to "organizational change" in the banking sector. Furthermore, it can be explained that the keywords identified, namely 208 keywords with 18 clusters, and the nine least common keywords in research related to "organizational change" in the banking sector are organizational change, banking sector, leadership, savings banks, knowledge management, readiness for change, and communication. This research has limitations because it only uses the Scopus database to analyze research topics, indicating that many studies with related topics have not been comprehensively mapped. Future research needs to conduct Bibliometric analysis using a wider database such as Google Scholar, Scient Direct, JSTOR, PubMed, Emerald Insight or Directory of Open Access Journals.